THE ROLE OF EDUCATION MANAGEMENT INFORMATION SYSTEMS (SIMDIK) IN IMPROVING LEARNING QUALITY IN SENIOR HIGH SCHOOL - Atabik Atabik; Khafifatul Fian (PT Altin Riset Publishing, 2024)
This paper aims to analyze the role of education management information systems in improving the quality of education in high schools. This type of writing is a literature study. Data is collected from various sources both books, websites, or scientific articles contained in Google Scholar. After the data is collected, data selection is carried out, and with concludes. Then the data is analyzed descriptively and continued with content analysis. The results showed that there are several roles of the education management information system in a school including as a tool in helping to improve educational standards, as an effort to mature humans so that they can get closer to the Creator through teaching and guidance which is a benchmark for the quality of education, helping in the operational process of schools that have been designed by current educational criteria, and support the smooth running of information that wants to get accurate results.